Bullies and Beakers: How Large Universities are Squashing Research Competition and the Contractual Remedies to Solve It - Jonathan Fort (Washington University Journal of Law & Policy, 2017)
This Note addresses the challenges that small research universities face when competition from larger, well-funded research universities lure highly skilled researchers using lucrative compensation packages and other benefits. Fort evaluates doctrines in contract law to identify trends in intellectual property ownership, relationships between research institutions and private sectors, and current case law to identify dis-incentivizing mechanisms that could curb competition that leaves small research universities with little recourse once researchers are poached. Fort recommends strict assignment agreements that would preserve an interest in patents and copyrights in favor of the smaller research institutions, in addition to liquidated damages provisions in employment agreements that would deter researchers from interrupting valuable research projects as well as generate funds that would allow these institutions to remain competitive in innovation.
Keywords: Bayh-Dole Act; BDA; legal ownership; employee intellectual property; small research university; research universities; research projects; contract law; intellectual property; liquidated damages